Association between adult attachment and mental health states among health care workers: the mediating role of social support - Yang, Yahui; Chen, Kaichao; Liang, Kaiwen; Du, Wanyi; Guo, Jiamei; Du, Lian (Frontiers in Psychology, 2024)
Background: To determine the relationships between attachment style, social support and mental health states ， as well as the mediation mechanism within this relationship，we conducted a survey among health care workers during the Coronavirus Disease 2019 (COVID-19) epidemic quarantine. Method: The survey assessed their mental health states, adult attachment style, social support and some other relevant information. Mental health states were represented by the overall state of sleep, physical and emotional assessment. A multiple mediator model was used to explain how social support could mediate the relationship between attachment and mental health states during COVID-19 quarantine.Results: Our findings revealed that 33.3% of the participants experienced emotional issues, 8.5% had sleep problems, and 24.9% reported physical discomfort. The direct effect of adult attachment styles on mental health states during COVID-19 quarantine was significant (c'= -0.3172; p < 0.01). The total indirect effect also showed statistical significance (ab = -0.1857; p < 0.01). Moreover, the total effect of adult attachment styles on mental health states was -0.5029 (c = -0.5029; p < 0.01). Subjective social support and utilization of social support play mediating roles in the relationship between attachment style and mental health states, respectively(ab 1 =-0.1287，95%CI: -0.9120 to -0.3341，ab 2 =0.0570， 95%CI: -0.4635 to -0.1132) .3 Conclusion: These findings highlight social support played a mediation role between attachment style and mental health states. Thus, offering social support during a crisis might be useful for those individuals with an insecure attachment.